Logística internacional de mercancías y su contribución en el desarrollo nacional: factores que impulsan su desarrollo - Sánchez Mercado, Álvaro Cristian (2019)
Since ancient times to the present, international trade has been and continues being a preponderant factor in the development of a society or nation, as were shown by the examples of the Phoenician Culture, the Florence of the Medici, England of the Victorian ageand the China of today. The development of trade at this level involves the development of an increasingly competitive International Logistics System, as a significant part of the value of a product is constituted by its logistics cost and while the more developed it is, the most efficient it will be, and thus lower costs associated with it. In this context, first an exploration is made of the main models that explain the development of the International Logistics Sector and then identify the variables described in these models that would be applicable to the reality of Peru. Finally, in order to make a subsequent Prospective Planning of the International Logistics Sector of Goods in Peru that promotes the decentralized development of the country and making use of the inducing variables for the strengthening of the previously identified sector, we will proceed to propose the map of the problem that shows the limitations to its development making use of the logical framework methodology.